2020
DOI: 10.4081/jphr.2020.1733
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Vegetable Intake 400 G/Day to Control Body Weight and Lipid Profile in Overweight Hyperlipidemia Menopausal Women

Abstract: Background: Indonesia suffers growing health problems like obesity, diabetes, and other metabolic syndromes with dietary habit as one of risk factors. To control the lipid and glycaemic profile, high fibre intake has been recommended. This study administered 400g/day vegetable intake with its fiber contents and observed the effects in lipid profile and glycaemic control.Design: A parallel study of 30 pairs of menopausal women match paired in overweight, menopause, hyperlipidaemia, age, etc randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…The diet is also known as a possible way to prevent metabolic disorders. The use of daily intake of vegetables was investigated in a study [ 25 ]. A diet including 400 g per day of vegetables contributed to a better lipid profile and provided a sufficient intake of energy.…”
Section: Discussionmentioning
confidence: 99%
“…The diet is also known as a possible way to prevent metabolic disorders. The use of daily intake of vegetables was investigated in a study [ 25 ]. A diet including 400 g per day of vegetables contributed to a better lipid profile and provided a sufficient intake of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence on the effects of vegetable intake on metabolic risk factors are mainly from observational studies or small randomized controlled trials, and showed substantial inconsistency. For serum lipids, a randomized crossover study of ten healthy individuals reported that a diet high in vegetable reduced serum LDL and HDL [31], similar to a randomized trial reporting that increasing vegetable intake from 94 g/day to 400 g/day for 3 weeks reduced TC, LDL, HDL and BMI among 60 overweight Asian women [32]. However, another randomized trial with a larger sample size (n = 76) showed no effects on serum lipids and lipoproteins during 8 weeks [11], consistent with a large cross-sectional study showing no association with hyperlipidemia [12].…”
Section: Discussionmentioning
confidence: 99%
“…[ 91 ] The usual dietary intake of the participants was most commonly assessed at baseline in weight loss trials. A total of nine studies assessed usual dietary intake by administering 24-hour dietary recall (three weekdays and one weekend)[ 92 ] Women’s Health Initiative FFQ,[ 89 ] Vioscreen (an electronic FFQ),[ 44 ] four-day food record[ 48 ] and dietary food logs. [ 83 ] The frequency, type and distribution of meals were assessed via a meal pattern assessment grid in two studies.…”
Section: Discussionmentioning
confidence: 99%